Endogenous ochronosis with keratoelastoidosis marginalis - R Mythreyi; Adikrishnan Swaminathan; Anuradha Priyadarshini; Sudha Rangarajan; S Murugan (Wolters Kluwer Medknow Publications, 2019)
Endogenous ochronosis is a manifestation of alkaptonuria, a rare metabolic disease due to homogentisic acid oxidase deficiency. Darkened urine and arthropathy are the other two components that complete the triad of alkaptonuria. Pigmentation of skin, the presenting feature, is common over the face and ears. A few cases of pigmentation of the palms and soles are reported. Here, we report a case of endogenous ochronosis presenting as keratoelastoidosis marginalis, which is a rare manifestation.